2013
DOI: 10.4093/dmj.2013.37.5.343
|View full text |Cite
|
Sign up to set email alerts
|

Hemoglobin A1c May Be an Inadequate Diagnostic Tool for Diabetes Mellitus in Anemic Subjects

Abstract: BackgroundRecently, a hemoglobin A1c (HbA1c) level of 6.5% has been determined to be a criterion for diabetes mellitus (DM), and it is a widely used marker for the diagnosis of DM. However, HbA1c may be influenced by a number of factors. Anemia is one of the most prevalent diseases with an influence on HbA1c; however, its effect on HbA1c varies based on the variable pathophysiology of anemia. The aim of this study was to determine the effect of anemia on HbA1c levels.MethodsAnemic subjects (n=112) and age- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
1
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(33 citation statements)
references
References 18 publications
2
29
1
1
Order By: Relevance
“…HbA1c may be unreliable to diagnose prediabetes and diabetes in anaemic patients. Son et al found that anaemic subjects had a higher HbA1c level and suggested that the diagnostic significance of HbA1c may be limited in them [31]. This higher HbA1c was more pronounced in subjects with higher glucose levels.…”
Section: Discussionmentioning
confidence: 94%
“…HbA1c may be unreliable to diagnose prediabetes and diabetes in anaemic patients. Son et al found that anaemic subjects had a higher HbA1c level and suggested that the diagnostic significance of HbA1c may be limited in them [31]. This higher HbA1c was more pronounced in subjects with higher glucose levels.…”
Section: Discussionmentioning
confidence: 94%
“…They also suggest that IDA changes the quaternary structure of Hb leading to increased glycation. [15] grouped 329 Korean participants, not previously known to have diabetes, by diabetes status according to OGTT results. Participants were grouped as normal, prediabetes or diabetes, HbA 1c levels were then compared in each group for both anaemic and non-anaemic participants.…”
Section: Narrative Analysis Of Included Studiesmentioning
confidence: 99%
“…Recently, a review described the controversies concerning the role of anaemia on HbA 1c . In fact, some studies suggested that in patients with or without diabetes, iron deficiency anaemia (IDA) is associated with higher HbA 1c levels . Other works reported that, in patients not affected by diabetes but with iron deficiency, HbA 1c concentrations had no significant changes .…”
Section: Introductionmentioning
confidence: 99%
“…observed that HbA 1c level in subjects with IDA was significantly lower than in the control group . Few works evaluated the relationship between erythrocyte indices and HbA 1c levels; in particular, statistical analyses were unclear or not assessed . Koga et al .…”
Section: Introductionmentioning
confidence: 99%